Evaluating financial performance ratio analysis and common-size financial statement analysis for five years (2006-2010) Petronas Gas Berhad / Nabihah Mohammad - Mohammad, Nabihah (Faculty of Business and Management, 2011)
This research paper is focused to study the financial performance of Petronas Gas Berhad. The reason is because the stability of one company is depending on their financial performance and how they utilize it for the company benefits. They can operate effectively and effeciently by having good financial performance. There are a lot of methods that can be used to analyze the company performance but the researcer will focus on commmon size and ratio analysis. Then from this study,the reseacher hopes that, it will give her better understanding on how company performance based on their financial statement.